Video Game Self-efficacy and its Effect on Training Performance - Skilan A. Ortiz; Clint A. Bowers; Janis A. Cannon-Bowers (Serious Games Society, 2015)
This study examined the effects of using serious games for training on task performance and declarative knowledge outcomes. The purpose was to determine if serious games are more effective training tools than traditional methods. Self-efficacy, expectations for training, and engagement were considered as moderators of the relationship between type of training and task performance as well as type of training and declarative knowledge. Results of the study offered support for the potential of serious games to be more effective than traditional methods of training when it comes to task performance.